2021
DOI: 10.3390/beverages7030046
|View full text |Cite
|
Sign up to set email alerts
|

Adapting Polarized Projective Mapping to Investigate Fruitiness Aroma Perception of White Wines from Oregon

Abstract: Fruitiness is a highly desirable aroma quality in white wines. This study aimed to investigate the fruitiness aroma perception of white wines using a rapid sensory method and to compare the sensory maps obtained from wine experts and trained consumers. A polarized projective mapping (PPM) method was adapted by using fruit standards as fixed poles. Twenty-one white wines were selected for this study. Ten wine experts and twelve trained consumers participated in the adapted PPM followed by ultra-flash profiling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
(74 reference statements)
0
6
0
Order By: Relevance
“…However, some studies used more than 12 samples. For example, Iobbi and Tomasino (2021) asked experts and trained panelists to evaluate 21 white wines, whereas Heymann, Hopfer, and Bershaw (2014) asked experts to evaluate 19 white wines. In general, the more training or more knowledge that participants have, the more samples that are then included in the study.…”
Section: Resultsmentioning
confidence: 99%
“…However, some studies used more than 12 samples. For example, Iobbi and Tomasino (2021) asked experts and trained panelists to evaluate 21 white wines, whereas Heymann, Hopfer, and Bershaw (2014) asked experts to evaluate 19 white wines. In general, the more training or more knowledge that participants have, the more samples that are then included in the study.…”
Section: Resultsmentioning
confidence: 99%
“…This distinction can also be seen in wines, where Chardonnay may be considered less complex than a Chardonnay Riesling blend, but wine would still be considered a complex product category. This distinction is important because previous research has shown that attempts to eliminate all ambiguity by using single aroma reference standards with a complex product category, such as wine, have not been sufficient to capture the diversity of the product set (Iobbi & Tomasino, 2021). These results suggest that poles used to describe complex product sets may work best if they are the simplest examples of the product category, while still belonging to the product category.…”
Section: Discussionmentioning
confidence: 99%
“…Of the two studies looking at PPM in more complex products, in this case wine, only one has focused on pole selection. This study by Iobbi and Tomasino (2021) investigated the use of aroma reference standards as poles. While the study demonstrated that it was possible to place wines using these poles, the results were not as clearly separated as the researchers anticipated and potential dumping effects were observed when characteristics in the wines were not present in the poles.…”
Section: Introductionmentioning
confidence: 99%
“…The volatile thiols 3-MH, 3-MHA and 4-MMP are well known for exclusively imparting these aromas in white wines [ 27 , 28 ]. However, recent studies have shown the perception of tropical fruit aroma in white wines which the presence of these varietal compounds are less prominent [ 16 , 20 , 29 , 30 ]. This brings to light the fact that other volatile compounds may also cause tropical fruit aroma.…”
Section: Discussionmentioning
confidence: 99%